Factors associated with needle-stick injuries among healthcare workers in tertiary care hospital: A cross-sectional analytical study. - Seema Yasmeen; Rabia Abbas; Ali Altaf; Ayesha Muzaffar; Saba Muazzam; Hafiza Naima Anwar (The Professional Medical Journal, 2026)
Objective: To determine the 12-month frequency of self-reported needle-stick injuries (NSIs) among healthcare workers, identify associated demographic and occupational risk factors, and evaluate post-exposure care and management practices. Study Design: Analytical Cross-sectional study. Period: January to June 2025. Setting: Shahida Islam Teaching Hospital. Methods: Using stratified random sampling, 379 eligible clinical staff members were recruited. Data were collected via structured, WHO/CDC-adapted questionnaires assessing demographics, injury circumstances, and safety protocols. Bivariate analyses and multivariable binary logistic regression were performed to isolate independent predictors of NSIs while controlling for confounding variables. Results: The 12-month NSI prevalence was 46.2% (n=175). Hollow-bore needles were the most frequently implicated devices (52.6%), primarily during blood withdrawal. Formal incident reporting was suboptimal at 54.3%, with fear of reprimand and heavy clinical duties cited as primary barriers. Multivariable analysis demonstrated that working night or rotating shifts (aOR=2.14), high perceived workload (aOR=1.89), and lacking safety training within the preceding year (aOR=2.85) significantly elevated injury risk. Conversely, possessing five or more years of clinical experience emerged as a strong protective factor (aOR=0.45). Conclusion: NSIs remain a substantial occupational hazard in tertiary care environments, predominantly driven by inadequate safety training, night-shift fatigue, and heavy workloads. Implementing mandatory, hands-on safety reinforcement alongside non-punitive, simplified reporting mechanisms is urgently required to mitigate risks and improve overall post-exposure management.